Topological defects in f(T) theory of gravity - S. P. Hatkar; D. P. Tadas; S. D. Katore (European Physical Journal C: Particles and Fields)
Abstract In this paper, we investigate the behaviour of domain walls and one-dimensional cosmic string with locally rotationally symmetric (LRS) Bianchi type-I metric in the context of f(T) gravity. Three different types of deceleration parameter (DP) forms, such as (i) $$q=-kt+l-1$$ q = - k t + l - 1 , (ii) $$q=b(t)$$ q = b ( t ) , and (iii) $$q=-1+\frac{γ }{1+a^γ }$$ q = - 1 + γ 1 + a γ , are used to determine the exact solution of the field equation. We observe the profound effect of the torsion scalar T on physical parameters. Also, the universe was dominated by string at an early stage of evaluation.